Production of Granular cold water soluble Sago starch and related instant food products - Lee, Jau Shya (Universiti Malaysia Sabah, 2010)
The main objective of this study was to produce laboratory scale granular cold water soluble sago starch with high cold water solubility and improved granularity. The study was started by using Response Surface Methodology (RSM) and a two-factor three-level Faced-Centered Cube (FCD) Design to optimize the amount of NaOH and ethanol concentration to produce GCWS sago starch. The optimum conditions consisted of 40.7-50.5% ethanol and 278.5-296.3 g NaOH which achieved 52.2 ± 1.5% of cold water solubility. Later, alcoholic-alkaline treatment was combined with three types of chemical modification, namely hydroxypropylation, cross-linking and dual-modification to produce modified GCWS sago starch. RSM was used to investigate the effect of process variables and their interaction on the responses studied. Both cross-linking and dual modification were successfully improved the cold water solubility (> 60% and> 80% respectively) and granularity of instant sago starch produced. However, the functionalities (pasting and thermal behavior) of instant starch produced were found different due to the structural alteration took place in the starch granules. Hydroxypropylation did not affect the cold water sweIJing power and solubility of GCWS sago starch (p>0.05), but improved the retrogradation by reducing the setback. In brief, all treatments share the fact that NaOH was the most important variable affecting the responses studied. Modified GCWS sago starch produced had been developed as instant thickener in instant cocoa filling and topping premix for bakery and confectionary products. The cost needed in preparation of this modified GCWS sago starch is somehow very expensive due to high wastage during washing process.